Особенности изменения теплофизических и физико-механических свойств наполненного акрилоксида в процессе полимеризации - Литвиненко, Евгения Игоревна; Авраменко, Вячеслав Леонидович (НТУ "ХПИ", 2004)
The basic features of changing of relax conditions of polymerizing ackryloxide are searched according to data of calorimetric, reoviscosimetrical, dynamic and mechanical tests depending on polymerization process from viscous fluid to solid glass-type state. Characteristic differences of increase of viscosity of the filled system are resulted depending on a kind of the used modifier for a surface of a disperse phase. The specified features are closely connected to display of microheterogeneity binding during polymerization that d efines(determines) time of stabilization of elastic parameters of a composite
Keywords: акрилоксид ТУ 60-22-124-82; цеолит; синтетический алюмосиликат; скорость тепловыделения